Influence of Pain Sensitivity on Surgical Outcomes After Lumbar Spine Surgery in Patients With Lumbar Spinal Stenosis. Issue 3 (1st February 2015) - Kim, Ho-Joong; Lee, Jeong-Ik; Kang, Kyoung-Tak; Chang, Bong-Soon; Lee, Choon-Ki; Ruscheweyh, Ruth; Kang, Sung Shik; Yeom, Jin S.
Abstract : Study Design: Prospective observational study. Objective: To assess the influence of pain sensitivity on surgical outcomes after lumbar spine surgery in patients with lumbar spinal stenosis (LSS). Summary of Background Data: No previous study has investigated the relationship between the surgical outcomes for LSS and pain sensitivity questionnaire (PSQ) scores. Methods: The study included 171 patients who were scheduled to undergo spine surgery for LSS. On the basis of their PSQ scores, patients were assigned to either a low (PSQ score <6.5, n = 87) or high PSQ group (PSQ score ≥6.5, n = 84). The primary outcome was the Oswestry Disability Index (ODI) at 12 months after surgery. Results: The ODI at 12 months after surgery was significantly lower in the low PSQ group than in the high PSQ group. Twelve months after surgery, the mean ODI scores (95% confidence interval) in the low and high PSQ groups were 21.1 (16.8–25.5) and 29.6 (25.0–34.1), respectively. The difference (95% confidence interval) in the ODI between the 2 groups was 3.2 (−14.7 to −2.2) ( P = 0.009). There were significant differences in the secondary endpoints, including the ODI and visual analogue scale (VAS) scores for back and leg pain, in the follow-up assessments during a 12-month period after surgery, between the 2 groups (PSQ group; P < 0.001 for the ODI, VAS score for back pain, and VAS score for leg pain). However, the patterns of changes of the ODI and VAS scores for back pain and leg pain in the follow-up assessments during a 12-month period were not significantly different (interaction between the PSQ group and follow-up assessment time; P = 0.757, 0.126, and 0.950, respectively). Conclusion: Patients with high pain sensitivity may display less improvement in back pain, leg pain, and disability after surgery for LSS compared with patients with low pain sensitivity. Furthermore, the PSQ can be used to predict surgical outcomes after spine surgery for LSS. Level of Evidence: 2 Abstract : An individual's pain sensitivity can influence their surgical outcomes for lumbar spinal stenosis; and patients with lumbar spinal stenosis who have high pain sensitivity experience less improvement in back pain, leg pain, and disability after surgery compared with patients with low pain sensitivity.